Synthesis by wet chemical method of different phases of apatites applying ultrasound - Rodriguez-Chanfrau, Jorge E. [UNESP]; Garcia Pelizaro, Thales A. [UNESP]; Da Silva, Ricardo Moutinho [UNESP]; Tolaba, Angel G.; Pizoni, Elizabeth [UNESP]; Veranes-Pantoja, Yaymarilis; Guastaldi, Antonio C. [UNESP] (American Scientific Publishers, 2018)
Calcium phosphates have been widely used in medical, orthopedic and dental applications as materials for the replacement and repair of bone tissue or as implants coatings. Hydroxyapatite (HA), one of the phases of the Apatite, is one of the most used material for these applications due to its bioactivity and biocompatibility and similarity with the mineral phase of the human bone. One of the most widely methods used in calcium phosphate synthesis is the wet method, which allows to modify the physical chemical properties of the HA through the adjust of technical parameter of the method. The aim of this work was to study the influence of ultrasound during the maturation stage of the synthesis process. The obtained samples were characterized by X-ray Powder Diffraction, FTIR spectroscopy and Scanning Electron Microscopy. Particle size by scanning electron microscopy was determined. The calcium content by atomic absorption spectrometry was determined. The absorption/ desorption isotherms were determined by the method of nitrogen adsorption surface area, and the porosity was determined. The obtained results were compared with the results obtained in the synthesis without applying ultrasound. In this work ACP, TCP and OCP calcium phosphate were obtained by a wet reaction, without and with application of ultrasound. All samples shown isotherms adsorption/desorption characteristic of mesoporous materials. The samples treated with ultrasound have smaller particle size, smaller pore size and smaller surface area than samples obtained without ultrasound application.
Keywords: Absorption/Desorption Isotherms; Calcium Phosphate; Particle Size; Surface Area; Ultrasound